Discourse on the Gender Subject and Olympic Sports (in Greek). Ο Προβληματισμός περί έμφυλου υποκειμένου στον Ολυμπιακό Αθλητισμό. - Irene Kamberidou; Patsantaras, Nikolaos (Announcement at the "13th International Conference on Physical Education and Sport" of the Democritus University of Thrace{\c{}}May 20-22, 2005, Komotini, Greece, 2005)
Καμπερίδου Ει. & Πατσαντάρας Ν. (2005). Ο Προβληματισμός περί έμφυλου υποκειμένου στον Ολυμπιακό Αθλητισμό. Άθληση & Κοινωνία, Περιοδικό Αθλητικής Επιστήμης, 20-22, Μαίου 2005. ΤΕΦΑΑ του Δημοκρίτειου Πανεπιστημίου Θράκης, Κομοτηνή: 55-56. [L. 3 in Apella] **** Kamberidou, I., & Patsantaras, N. (2005). The Gender Subject in Olympic Sports . In Announcement at the "13th International Conference on Physical Education and Sport" of the Democritus University of Thrace, May 20-22, 2005, Komotini, Greece, published in SPORT & SOCIETY, Sport Science Journal, pp. 55-56. (in Greek) [L. 3 in Apella]